Children and adolescents' exposure to food and beverage marketing in social media apps. Issue 6 (28th January 2019) - Potvin Kent, Monique; Pauzé, Elise; Roy, Elisabeth‐Anne; de Billy, Nicholas; Czoli, Christine
Summary: Background: Unhealthy food marketing is a powerful determinant of unhealthy diets and obesity among children. Although it is known that food marketers target young people on social media, no study has yet quantified children's exposure on these platforms. Objectives: To compare the frequency and healthfulness of food marketing seen by children and adolescents on social media apps as well as estimate their weekly exposure. Methods: 101 children and adolescents (ages 7‐16 years) completed a survey on their media use and were recorded using their two favourite social media apps for 5 minutes each on the mobile device they usually use. Recordings of app use were reviewed to identify food marketing exposures. Results: Overall, 72% of participants were exposed to food marketing. Of the 215 food marketing exposures identified, most promoted unhealthy products such as fast food (44%) and sugar‐sweetened beverages (9%). Adolescents viewed more instances of food marketing, on average, per 10‐minute period compared with children (Mean [ SD ] = 2.6 [2.7] versus 1.4 [2.1], U = 1606, z = 2.94, P = 0.003). It was also estimated that children and adolescents see food marketing 30 and 189 times on average per week on social media apps, respectively. Conclusions: Statutory regulations restricting unhealthy food marketing to adolescents and children on social media should be considered.